Quantum free energies of the conformers of glycine on an ab initio potential energy surface - Miller, T; Clary, D (2004)
The torsional path integral Monte Carlo (TPIMC) technique is used to study the five lowest-energy conformers of glycine. The theoretical method provides an anharmonic and quantum-mechanical description of conformational free energy and is used for the first time with an ab initio potential energy surface. The 3-dimensional torsional potential energy surface of glycine was obtained at the MP2/6-311++G** level of theory and is optimized with respect to the non-torsional degrees of freedom. Calculated conformer populations compare well with those reported in recent matrix-isolation infrared spectroscopy experiments. An additional conformer, not yet observed, is predicted to be heavily populated in the thermal equilibria probed by experiment, and a new explanation for its elusiveness is provided. Quantum effects, such as zero point energy, are found to substantially alter conformer populations, and an algorithm for estimating the role of non-torsional vibrations in the conformational thermodynamics of a molecule is introduced.